Ameliorating effect of antioxidants and pregabalin combination in pain recurrence after ductal clearance in chronic pancreatitis: Results of a randomized, double blind, placebo‐controlled trial. Issue 9 (25th September 2016) - Talukdar, Rupjyoti; Lakhtakia, Sundeep; Reddy, D Nageshwar; Rao, G Venkat; Pradeep, Rebala; Banerjee, Rupa; Gupta, Rajesh; Ramchandani, Mohan; Tandan, Manu; Murthy, H Vivekananda
Abstract: Background and Aim: The aim of this study was to evaluate the effect of antioxidant–pregabalin combination on pain recurrence in patients with chronic calcific pancreatitis. Methods: In this randomized, double‐blind, placebo‐controlled trial, chronic calcific pancreatitis patients with pain recurrence following pancreatic ductal clearance of stones received either antioxidant‐pregabalin combination or matching placebo for 2 months followed by open‐label antioxidants for the next 4 months in both groups. Compliance, daily pain, and adverse events were recorded weekly and at the end of study by a coordinator blinded to treatment status. Primary outcome was pain improvement (visual analog scale and Izbicki score); secondary outcomes were as follows: complete pain resolution, painful days, and adverse events. Number needed‐to‐treat was calculated. Results: We randomized 42 and 45 patients (mean age 29.3 years) to treatment and placebo arms, respectively. Baseline characteristics, including pain scores, were similar for both groups. No patients received high‐potency narcotic. At 2 months, a significant improvement in the treatment arm was observed in percent reduction of visual analog scale (−50 [−80.0; −32.1] vs −29.5 [−64.5; 0]; P = 0.01), Izbicki score (14.5 [0; 21.3] vs 30.0 [11.8; 41.3]; P = 0.001), complete pain resolution (20 [47.6%] vs 12 [26.7%]; P = 0.04), and number of painful days (10.0 [2.0; 16.0] vs 18.0 [7.0; 34.0]; P = 0.01). Needed‐to‐treat was 4.8. Pain reduction persisted at 6 months in the original treatment group (20.0 [15.0; 28.0] vs 36.0 [20.0; 50.0]; P = 0.006). A total of 33 patients in the treatment arm experienced mild to moderate self‐limiting nausea/vomiting and drowsiness, respectively and did not require any change in study protocol. Conclusion: Antioxidant–pregabalin combination results in significant relief in pain recurrence after ductal clearance in narcotic naïve patients with chronic calcific pancreatitis.